Nanoarchitectonics of photothermal materials to enhance the sensitivity of lateral flow assays - Sarathkumar, Elangovan; Anjana, Rajasekharan S.; Jayasree, Ramapurath S. (Beilstein Journal of Nanotechnology, 2023)
Lateral flow assays (LFAs) are currently the most widely used point-of-care testing technique with remarkable advantages such as simple operation, rapid analysis, portability, and low cost. Traditionally, gold nanoparticles are employed as tracer element in LFAs due to their strong localised surface plasmon resonance. However, this conventional LFA technique based on colorimetric analysis is neither useful to determine critical analytes with desired sensitivity, nor can it quantify the analytes. Various signal amplification strategies have been proposed to improve the sensitivity and the quantitative determination of analytes using LFAs. One of the promising strategies is to enhance the photothermal properties of nanomaterials to generate heat after light irradiation, followed by a temperature measurement to detect and quantify the analyte concentration. Recently, it has been observed that the nanoscale architecture of materials, including size, shape, and nanoscale composition, plays a significant role in enhancing the photothermal properties of nanomaterials. In this review, we discuss the nanoarchitectonics of nanomaterials regarding enhanced photothermal properties and their application in LFAs. Initially, we discuss various important photothermal materials and their classification along with their working principle. Then, we highlight important aspects of the nanoscale architecture (i.e., size, shape, and composition) to enable maximum light-to-heat conversion efficiency. Finally, we discuss some of the recent advances in photothermal LFAs and their application in detecting analytes.
Keywords: lateral flow assay; nanoarchitectonics; photothermal; photothermal nanomaterials; signal amplification